Effectiveness of Village Financial Information System in Improving Financial Management Accountability: a Study in Paokmotong Village, East Lombok Regency - Syakila, Nur’ Ain; Martiningsih, Rr. Sri Pancawati (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyze the role of the Village Financial System (SISKEUDES) in improving financial management accountability in Paokmotong Village. This system is designed to improve village financial governance to be more transparent, accountable, and effective. In this study, a qualitative method with a descriptive approach was used to obtain data from observations, interviews, and documentation with village officials who play a role in village financial management. The results of the study indicate that the implementation of SISKEUDES has had a positive impact on village financial management, including increasing budget transparency, administrative order, and more accurate reporting. In addition, SISKEUDES also assists village officials in monitoring budget realization and reducing the risk of misappropriation of funds. Thus, SISKEUDES is effective in supporting financial management accountability in Paokmotong Village, and is recommended to be adopted by other villages to achieve better financial management.